Changes in Children’s Play During COVID-19 Pandemic: Parents’ Views - Pala, Şengül; Coşgun, Ayşegül Akıncı; Yılmaz, Aynur (FSM Vakıf Üniversitesi, 2022)
This study examines parents’ views on the changes in their children’s play at the beginning of the Coronavirus Disease 2019 (COVID-19) process. The study sample con sists of 38 parents, twenty mothers, and eighteen fathers who reside in different city cen ters (Trabzon, Istanbul, Bursa, and Ankara) in Turkey and have children between three and six. The data were collected with “demographic information form” and “open-ended question form” created by the researchers. Data were collected online via ‘Google For ms.’ Descriptive statistics were used in the analysis of the data. As a result of the research, it was found that children’s play differs according to the type of play, play area, material type, and playing time with parents. The change in the type of play consisted of an inc rease in pretend play, an increase in educational plays, an increase in board games, a increase in plays involving art activities, a decrease in play behaviors that requires being physically active, an increase in building plays, and an increase in science and nature knowledge plays. The change in material type consisted of an increase in the use of technological tools. The change in the play area consisted of a decrease in outdoor play and an increase in indoor play. These results are discussed with the relevant literature. Change in playing time with parents consisted of increase in playing with mother and increase in playing with father. These results are discussed within the framework of the relevant literature.

Bu çalışmanın amacı, Coronavirüs salgını (COVID-19) başlangıcı sürecinde çocuklarının oyunlarındaki değişikliklere ilişkin ebeveyn görüşlerini incelemektir. Araştırmanın çalışma grubunu Türkiye’nin farklı il merkezlerinde (Trabzon, İstanbul, Bursa ve Ankara) ikamet eden, üç ile altı yaş arasında çocuğu olan 38 ebeveyn (20 anne ve 18 baba) oluşturmaktadır. Veriler araştırmacılar tarafından hazırlanmış olan “Demografik Bilgi Formu” ve “Açık Uçlu Soru Formu” ile toplanmıştır. Veriler ‘Google Formlar’ aracılığıyla çevrimiçi olarak toplanmıştır. Verilerin analizinde betimsel analiz kullanılmıştır. Araştırma sonucunda, salgın sürecinde çocukların oyunlarının “oyun türü, oyun alanı, materyal türü ve ebeveynlerle oynanan zaman” açısından farklılaştığı belirlenmiştir. Oyun türündeki değişimin incelendiğinde, sembolik oyunlarda artış, eğitsel oyunlarda artış, masa başı oyunlarda artış, yapı oyunlarında artış, sanata dayalı oyun etkinliklerinde artış, fiziksel olarak aktif olmayı gerektiren oyunlarda azalış, bilim ve doğa bilgisi oyunlarında artıştan oluştuğu belirlenmiştir. Oyun alanındaki değişim açık hava oyunlarında azalma ve kapalı alan oyunlarında artış olarak belirlenmiştir. Materyal türündeki değişim ise teknolojik araç kullanımında artışı kapsamaktadır. Ebeveynlerle oynama süresindeki değişim, anne ile oynamanın artması ve baba ile oynamanın artmasından oluşmuştur. Bu sonuçlar ilgili literatür çerçevesinde tartışılmıştır.
COVID-19 Salgını Sırasında Çocukların Oyunlarındaki Değişiklikler: Ebeveyn Görüşleri
Keywords: COVID-19; Parents’ View; Play; Preschool Children; Ebeveyn Görüşleri; Oyun; Okul Öncesi Çocuklar